The potentials and limitations of tax dispute prevention and alternative resolution mechanisms - Kovač, Polonca, pravnica (Array, 2019)
This paper deals with prevention and alternative dispute resolution (ADR) in tax matters, particularly in the light of the specific nature of administrative relations, which also include tax procedures. Given the involvement of stakeholders, ADR benefits both the taxpayers and the tax authority, enabling greater legal certainty and speedier finalisation of procedures. Yet, ADR also poses an open threat to the public interest and equality as international and constitutional administrative principles, and must therefore be limited in tax procedures. This also derives from the legal acts of the EU and the Council of Europe. In addition to theoretical frameworks and types of dispute prevention and resolution mechanisms studied by means of scientific literature review, legal sources analysis and comparative insights, the paper presents the Slovenian regulation and practice of the Financial Administration (FURS) over the past years. The aim of this research is to examine the de iure and de facto situation at the national level. The analysis shows that, in tax matters, ADR is noticeably more intensive at the international level than within national tax systems. On the other hand, individual countries prefer to establish regulatory mechanisms for prevention, which should result in even more desired avoidance of disputes. It can be concluded that efficient tax procedures require an integrated approach, including both dispute prevention and ADR, in order to ensure the principles of tax justice and systemic inclusion of all stakeholders in its governance.